Analisis Uji Kuat Tekan Beton Menggunakan Agregat Lokal di Sungai Bogali Desa Hilisalo’o Kecamatan Sitolu Ori - Zega, Fa'aso; Telaumbanua, Arisman; Telaumbanua, Aprianus; Harefa, Envilwan Berkat (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2024)
Concrete compressive strength analysis is an important step in the design and manufacture of quality concrete. Selecting the right quality local aggregates, and conducting accurate aggregate testing, can optimise the strength of the concrete produced. In Hilisalo'o Village, Sitolu Ori Sub-district, there are many local aggregates in the form of stone and sand. This study aims to determine the compressive strength value of concrete using local aggregates in Bogali River, Hilisalo'o Village, Sitolu Ori Subdistrict. The method used in this research is experimental research. Based on the results of the 14-day-old concrete compressive strength test, the compressive strength value of concrete using local aggregates in Bogali River, Hilisalo'o Village, Sitolu Ori Subdistrict has a different average compressive value based on the working method, namely material (sand, gravel, cement, and water) without control (unwashed material) has a compressive strength value of 119.07 kg/cm2 (K-119 or 9.88 Mpa), material (sand, gravel, cement, and water) with control (washed material) has a compressive strength value of 180.48 kg/cm2 (K-180 or 14.98 Mpa) material (sand, crushed stone, cement, and water) without control (unwashed material) has a compressive strength value of 167.30 kg/cm2 (K-167 or 13.89 Mpa), and material (sand, crushed stone, cement, and water) with control (washed material) of 209.83 kg/cm2 (K-209 or 17.42 Mpa).  The results of the compressive strength test show that the materials (sand, gravel, cement and water) with the contract.